Penerapan Metode Preference Selection Index Dalam Pemilihan Teller Terbaik - Rizki, Muhammad; Ginting, Garuda (Forum Kerjasama Pendidikan Tinggi, 2020)
In the era of globalization which is laden with competition, good service quality is a concern for companies that want to continue to exist, especially companies in the service sector such as banks in Indonesia. Institutions with low service quality will be less desirable or even abandoned by customers. Therefore, identification of service quality characteristics is needed in an effort to improve service quality. One of them is the teller who plays the most important role in customer service. Of course the selection of the best tellers must be done as well as possible. Based on these problems, the PSI method used in this study is to determine the teller by considering aspects of the determination that has been determined by the Bank. The aspects of determination which are the basis of determination by the Bank in determining the best teller are attitude, skill and appearance. By using the PSI method it is expected to be able to assist the leadership of the CIMB Niaga Bank in determining the teller process so that it is faster and more effective. Become a reference for research related to the Bank.